ONLINE WRITING CLASS AT ENGLISH DEPARTMENT OF UIN PROF. K.H. SAIFUDDIN ZUHRI: THE IMPLEMENTATION AND THE STUDENTS’ PERCEPTIONS - Sinta Sekarini; Desi Wijayanti Marufah (Universitas Perjuangan Tasikmalaya, 2021)
The world is currently experiencing turmoil over the outbreak of the global pandemic Covid-19. To anticipate the transmission of the virus, the government has imposed an education policy for schools and universities to stop the offline learning process, and all activities are carried out online. Based on Circular No.002 of 2020 UIN Prof. K.H. Saifuddin Zuhri Purwokerto which explains that UIN Prof. K.H. Saifuddin Zuhri Purwokerto also implements online learning for all majors and all courses. Therefore, this study aims to analyse the use of e-learning in online writing class and students' perceptions of online writing class at the English Department of UIN Prof. K.H. Saifuddin Zuhri Purwokerto.This research used qualitative descriptive analysis method. The data that used is qualitative data and supported by quantitative data. Qualitative data is obtained from the result of interview, observation, and documentation. While the quantitative data is obtained from questionnaire. The interview was done with interviewing a lecturer of writing class. The researcher did the observation four times through online by joining online writing class of UIN Prof. K.H. Saifuddin Zuhri Purwokerto. Questionnaires were also given to students to analyse how their perception of the use of e-learning in an online writing class. Questionnaires were given to 2-TBI A and 4-TBI B students using Google Form. From the questionnaire, 44 student responses were obtained. The results of this research show that the online writing classes in UIN Prof. K.H. Saifuddin Zuhri Purwokerto used Google Classroom to submitting and correcting the students' assignments, Google Meet for virtual classes, Telegram for discussions, and ECLASS for distributing the lecture materials. Then, students felt hard to understand the material and lack to understand the teacher's instructions. Furthermore, the result showed that most of the students responded positively to the strategies of the teacher in the online writing class. Keywords: Students’ Perception, Online Writing Class, Writing Skill.